Biodegradable polyurethane scaffolds in regenerative medicine: Clinical translation review. Issue 8 (28th April 2022) - Pedersen, Drake D.; Kim, Seungil; Wagner, William R.
Abstract: Early explorations of tissue engineering and regenerative medicine concepts commonly utilized simple polyesters such as polyglycolide, polylactide, and their copolymers as scaffolds. These biomaterials were deemed clinically acceptable, readily accessible, and provided processability and a generally known biological response. With experience and refinement of approaches, greater control of material properties and integrated bioactivity has received emphasis and a broadened palette of synthetic biomaterials has been employed. Biodegradable polyurethanes (PUs) have emerged as an attractive option for synthetic scaffolds in a variety of tissue applications because of their flexibility in molecular design and ability to fulfill mechanical property objectives, particularly in soft tissue applications. Biodegradable PUs are highly customizable based on their composition and processability to impart tailored mechanical and degradation behavior. Additionally, bioactive agents can be readily incorporated into these scaffolds to drive a desired biological response. Enthusiasm for biodegradable PU scaffolds has soared in recent years, leading to rapid growth in the literature documenting novel PU chemistries, scaffold designs, mechanical properties, and aspects of biocompatibility. Despite the enthusiasm in the field, there are still few examples of biodegradable PU scaffolds that have achieved regulatory approval and routine clinical use. However, there is a growing literature where biodegradable PU scaffolds are being specifically developed for a wide range of pathologies and where relevant pre‐clinical models are being employed. The purpose of this review is first to highlight examples of clinically used biodegradable PU scaffolds, and then to summarize the growing body of reports on pre‐clinical applications of biodegradable PU scaffolds.